Elucidating the impact of Hypericum alpestre extract and L-NAME on the PI3K/Akt signaling pathway in A549 lung adenocarcinoma and MDA-MB-231 triple-negative breast cancer cells. - Hayarpi Javrushyan; Mikayel Ginovyan; Tigran Harutyunyan; Smbat Gevorgyan; Zaruhi Karabekian; Alina Maloyan; Nikolay Avtandilyan (PLoS ONE)
Plants of the Hypericaceae family have been traditionally used for their medicinal properties, including antibacterial, antiviral, and antioxidant activities. Among these, Hypericum alpestre (HA) extracts have shown notable cytotoxicity against various cancer cell lines, drawing attention to their phenolic compounds as potential anticancer agents. Similarly, N(G)-Nitro-L-arginine methyl ester (L-NAME), an inhibitor of nitric oxide synthase (NOS) activity, has emerged as a promising candidate in cancer therapy. However, the precise molecular mechanisms underlying the anticancer effects of both HA and L-NAME remain unclear. This study aimed to clarify the impact of HA and L-NAME on the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/ mammalian target of rapamycin (mTOR) signaling pathway in A549 human lung adenocarcinoma and MDA-MB-231 breast cancer triple-negative cells, with particular emphasis on the tumor necrosis factor-alpha (TNFα)/cyclooxygenase-2 (COX-2) and vascular endothelial growth factor A (VEGFα)/matrix metalloproteinase-2 (MMP-2) pathways. In silico analyses identified compounds within HA extracts with the highest affinity for PI3K/Akt, a finding subsequently confirmed by in vitro experiments. Notably, the combination of HA and L-NAME demonstrated greater efficacy than the combination of HA and 5-fluorouracil (5-FU), as evidenced by enhanced apoptotic activity. Both HA alone and in combination with L-NAME inhibited the TNFα/COX-2 and VEGFα/MMP-2 pathways. These results suggest that the therapeutic effects of HA, especially in combination with L-NAME, may be mediated through the PI3K/Akt signaling pathway. A better understanding of the interaction between HA polyphenols and PI3K/Akt signaling could pave the way for novel therapeutic strategies against cancer, including drug-resistant tumors.